2020
DOI: 10.1016/j.funeco.2020.100994
|View full text |Cite
|
Sign up to set email alerts
|

Grapevine pruning time affects natural wound colonization by wood-invading fungi

Abstract: Grapevine pruning wounds made during the dormant season are a port of entry of woodinvading fungi. Timing of pruning may affect the wound susceptibility to these fungi, such as those associated with grapevine trunk diseases (GTDs). This study aimed to determine the effect of pruning time on natural fungal infection in six vineyards in Galicia, Spain, belonging to three Denominations of Origin (D.O) over two growing seasons. Pruning wounds were left unprotected physically and chemically during two periods of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 70 publications
(64 reference statements)
7
27
0
Order By: Relevance
“…Similarly, Martinez‐Diz et al . (2020) found no significant differences between the diversity of fungal communities of grapevine wood samples in different sampling plots. Liu and Howell (2021) also reported that geographic location only slightly affected the microbial diversity and composition, except for fungal diversity associated with roots; however, regional and small‐scale variation in the below‐ground fungal microbiome is relatively common (Zarraonaindia et al ., 2015; Knight et al ., 2019; Deyett and Rolshausen, 2020).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Similarly, Martinez‐Diz et al . (2020) found no significant differences between the diversity of fungal communities of grapevine wood samples in different sampling plots. Liu and Howell (2021) also reported that geographic location only slightly affected the microbial diversity and composition, except for fungal diversity associated with roots; however, regional and small‐scale variation in the below‐ground fungal microbiome is relatively common (Zarraonaindia et al ., 2015; Knight et al ., 2019; Deyett and Rolshausen, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…Although various techniques are commonly used to assess OTU or amplicon sequence variant (Deyett and Rolshausen, 2019; Deyett and Rolshausen, 2020) numbers in fungal communities of grapevines using different primer sets (Pinto et al ., 2014) and sequencing techniques (Kernaghan et al ., 2017), our 853 OTUs of the filtered samples correspond to those of similar studies, in which the OTU number ranges between 200 and 2200 (e. g . Pinto et al ., 2014; Jayawardena et al ., 2018; Martinez‐Diz et al ., 2019, 2020; Fan et al ., 2020; Liu and Howell, 2021). Random subsampling of the samples to a few thousand reads is not unusual as seen in various analyses of fungal microbiomes of different above‐ground grapevine plant materials (Bokulich et al ., 2014, 2016; Pinto et al ., 2014; Fan et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last two decades, different approaches to manage leaf stripe symptoms and to reduce vine death due to diseases of Esca complex have been tested and applied in the field. After the phasing out of sodium arsenite in the early 2000s, the applied tools for managing leaf stripe symptoms have been diversified, including pruning timing and modes, wound protection, remedial surgery and foliar treatments using biostimulants or chemical products [30][31][32][33]. Among the remedial surgery treatments, trunk renewal and trunk surgery are the best-known methods.…”
Section: Introductionmentioning
confidence: 99%
“…An assay that evaluates the persistence of Trichoderma strains over a pruning wound will help to decide if these strains are suitable to be sprayed in field conditions. In order to reduce natural infection, early pruning (November) is recommended in combination with a biological or chemical wound protectant to reduce the risk of infection of Eutypa lata, Neofusicoccum parvum, Botryosphaeria dothidea, Phomopsis spp., Cryptovalsa ampelina, Phaeomoniella chlamydospore, Diplodia seriata [69], and the genera Botryosphaeria, Cadophora, Cryptovalsa, Cytospora, Diaporthe, Diplodia, Eutypa, Neofusicoccum, Phaeoacremonium, and Phaeomoniella [70] in comparison to late pruning (February) [57,58]. Moreover, delayed pruning may result in the sap-flow washing away any pruning wound protectant [53].…”
Section: Discussionmentioning
confidence: 99%